2017
DOI: 10.1051/0004-6361/201730551
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-compact structure in intermediate-luminosity radio quasars: building a sample of standard cosmological rulers and improving the dark energy constraints up to z ~ 3

Abstract: In this paper, we present a new compiled milliarcsecond compact radio data set of 120 intermediate-luminosity quasars in the redshift range 0.46 < z < 2.76. These quasars show negligible dependence on redshifts and intrinsic luminosity, and thus represents, in the standard model of cosmology, a fixed comoving-length of standard ruler. We implement a new cosmology-independent technique to calibrate the linear size of of this standard ruler as l m = 11.03 ± 0.25 pc, which is the typical radius at which AGN

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
191
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 127 publications
(211 citation statements)
references
References 86 publications
15
191
1
2
Order By: Relevance
“…On the one hand, the present value of the matter density parameter m given by quasars is much larger than that derived from other observations. This has been noted by our previous analysis of Cao et al [29] and the first-year Planck results, in the framework of CDM cosmology. Such a result indicates that quasar data at high redshifts may provide us a different understanding of the parameters describing the components of the Universe.…”
Section: Observational Constraintssupporting
confidence: 77%
See 3 more Smart Citations
“…On the one hand, the present value of the matter density parameter m given by quasars is much larger than that derived from other observations. This has been noted by our previous analysis of Cao et al [29] and the first-year Planck results, in the framework of CDM cosmology. Such a result indicates that quasar data at high redshifts may provide us a different understanding of the parameters describing the components of the Universe.…”
Section: Observational Constraintssupporting
confidence: 77%
“…The final results indicated that intermediate-luminosity quasars show negligible dependence on both redshifts z and intrinsic luminosity L, which makes them a fixed comoving-length standard ruler. More recently, based on a cosmologicalmodel-independent method to calibrate the linear sizes l m of intermediate-luminosity quasars, Cao et al [29] investigated the cosmological application of this data set and obtained stringent constraints on both the matter density m and the Hubble constant H 0 , which agree very well with the recent Planck results. The advantage of this data set, compared with other standard rulers, BAO [30][31][32], clusters [33], strong lensing systems [34][35][36]), is that quasars are observed at much higher redshifts (z ∼ 3.0).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Pioneer work using these data was also performed in Ref. [39] to probe a flat CDM model and the XCDM model, in which the linear size of this standard ruler was calibrated as l m = 11.03 pc through a cosmological-model-independent method. As complementary to other cosmological standard rods, such as BAO and galaxy clusters [40], quasars are promising objects for studying the expansion rate of the Universe at much higher redshift, and thus they have become an effective probe in cosmology and astrophysics [20,39].…”
Section: Introductionmentioning
confidence: 99%